Microstructure and ablation property of gradient ZrCSiC modified C/C composites prepared by chemical liquid vapor deposition. Issue 10 (July 2019) - He, Qinchuan; Li, Hejun; Wang, Changcong; Li, Tao; Lu, Jinhua
Abstract: Chemical liquid vapor deposition was adopted to fabricate gradient ZrCSiC modified C/C composites, and the microstructure and ablation resistance were studied. Results displayed the content of SiC decreased from the composites edge to the center but that of ZrC increased, indicating SiC and ZrC ceramics have the gradient distribution in the composites. The gradient composites possessed a low CTE and high thermal conductivity. The low CTE restricted the formation and expansion of defects, which could slow the oxygen diffusion in the composites. The high thermal conductivity could transfer the heat quickly in ablation process, which reduced the heat accumulation on the ablation surface and weakened the thermal erosion. Therefore, the gradient composites possessed an outstanding anti-ablation property at two heat fluxes. Compared with the uniformed distribution composites, the linear and mass ablation rates of the gradient composites decreased by 60.9% and 66.7% at heat flux of 2.38 MW/m 2 and decreased by 55.9% and 67.2% at heat flux of 4.18 MW/m 2 . Because of the gradient distribution, porous ZrO2 coating, ZrO2 SiO2 coating and SiO2 coating with SiO2 nanowires were generated on the ablation center, ablation transition zone and ablation edge, respectively. These coatings isolated the sample surface from the flame and inhibited the transport of oxygen into the sample inner.